POLITICAL ETHICS IN BERGER DIALECTICS AGAINST THE MEANING OF POWER OF THE SOUTH NIAS DPRD MEMBERS FOR THE 2014-2019 PERIOD - Hadirat Manao (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The establishment of South Nias Regency is of course accompanied by the formation of new legislatif and executive institutions to run the government. The formation of these institutions provided an opportunity for the emergence of local Nias Selatan elites to take up positions as legislators and regional heads. Reflecting from the above view, this research is a case study that focuses on developing in-depth descriptions and explanations of the meaning of the position of legislatif members in South Nias in 2014. specifically the perspective of Peter L Berger's social construction.At a practical level, this study can be a "mirror" for local political elites in South Nias to understand the political dynamics in the district more sharply and deeply, and can be considered in formulating more appropriate strategies and tactics.The method in this study uses the phenomenology approach. This approach prioritizes human existence as something that must be interpreted or interpreted. Phenomenology in this study basically seeks to uncover and describe the meaning of the position of DPRD members for competing local South Nias elites. The conclusions in this study reveal that the reality of the meaning of office is in the view of members of the South Nias DPRD, namely as a mandate, arena of contestation, and aspects of interests. The factors underlying the interest of South Nias DPRD members towards positions were formed in two spheres, namely the individual domain and the community domain. In the individual domain, their interest in the position is motivated by four factors, namely internal motivation, external motivation, skills, and goals. While in the community domain there are three factors, namely the previous orientation, current orientation, and future orientation. The motive of South Nias DPRD members in choosing to become officials in the ranks of the government bureaucracy is to become a direct actor in South Nias regional development. Being an official for members of the South Nias DPRD is important than that position held by people who do not care about the development of South Nias. If the position is held by people who do not understand the history, culture and customs of South Nias, it will be fatal.